Ciudadanía gaditana, tributación y territorialidad en la Audiencia de Quito: el censo constitucional de 1813 y el plan de elecciones - Cabrera Hanna, Santiago (2018)
This article is a preliminary study of the forms which took the Cadiz citizenship in the audience of Quito, in 1813. The central argument of the article is that such citizenship was based on the Bourbon efforts of peripheral incorporation for tax purposes. Census records ordering by the monarchy in order to turn the tax collection more efficient and expand the tax mass were the basis of the constitutional census exercises, whose objective was to determine the number of citizens in each district to integrate new municipalities that had as purpose the conduct of elections. The contribution studies the 1813 census, ordered by Torivio Montes, and the Plan of Elections for the audience of Quito.